ANALYZING THE CHALLENGES OF DENTAL IMPLANTS: A COMPREHENSIVE CRITICAL REVIEW - 1- Metaib Abdullah Aldhalai, 2- Saleh Ali Saed, 3- Abdullah Ali said Al alharith, 4- Mansour Mahdi Alyami, 5- Mohammed Mana Alsagri, 6- Mahdi Mohammed Alkazman, 7- Abdullah Saleh A Alyami (Chelonian Research Foundation, 2023)
This critical review delves into the multifaceted challenges associated with dental implants, a cornerstone in restorative dentistry for replacing missing teeth. Despite their high success rates and widespread acclaim for restoring functionality and aesthetics, dental implants are not devoid of complications. This article systematically examines the literature to highlight the prevalent issues, including peri-implantitis, implant failure, and procedural complications, while also considering patient-specific factors like bone density and lifestyle habits that influence implant success. Additionally, the review explores the psychological impact on patients and the financial considerations involved. Through a comprehensive analysis, this article aims to provide a balanced perspective on dental implants, acknowledging their benefits while critically assessing the barriers to their universal applicability and long-term viability. By synthesizing recent research findings and expert opinions, this review offers valuable insights for both dental practitioners and patients contemplating dental implant treatments, encouraging informed decision-making and tailored patient care. Keywords: Dental Implants, Peri-implantitis, Implant Failure, Procedural Complications, Bone Density, Psychological Impact, Financial Considerations, Restorative Dentistry.